Structure, physiognomy and floristic composition of a Schinopsis balansae (Anacardiaceae) forest in the Southern Chaco, Argentina - Lewis, Juan Pablo (1997)
Amazonia and the Gran Chaco are the largest phytogeographic units of tropical and subtropical South America. The Santa Fe Forest Wedge is the southernmost portion of the Eastern Chaco, where the Schinopsis balansae forest (Quebrachal) is the most widespread and characteristic community. A detailed analysis of the floristic composition, physiognomy and vegetation structure was carried out in 32 10x10 m contiguous plots sampled along two transects in one of the these forests near Vera. Province of the Santa Fe, Argentina. All woody individuals 0.6 m present in the plots were recorded, identified and there their height and crown diameter measured. With These data, cartographic diagrams and vegetation profiles were drawn. Woody species were classified according to leaf size, leaf texture, presence of spines and phenology. This quebrachal is an open forest of very complex structure and heterogeneous floristic composition. The majority of woody species in this forest are deciduous, with small leaves and often with spiny structures. It has two high arboreal strata of S. balansae and Acacia praecox. and one arboreal low of Achatocarpus praecox with juvenile individuals of the species of the upper strata. There is also a shrub layer 2 m high. The arboreal canopy is discontinuous and has openings that can be quite large, where the ground is covered by a dense, grainy layer. This forest is similar to other S balansae forests of the Santa Fe Forest, but very different from most forests in other areas of the Gran Chaco.